Genetic variations in the DNA replication origins of human papillomavirus family correlate with their oncogenic potential - Yilmaz, Gulden; Biswas-Fiss, Esther E.; Biswas, Subhasis B. (Biochimica et biophysica acta. General subjects, 2018)
Human papillomaviruses (HPVs) encompass a large family of viruses that range from benign to highly carcinogenic. The crucial differences between benign and carcinogenic types of HPV remain unknown, except that the two HPV types differ in the frequency of DNA replication. We have systematically analyzed the mechanism of HPV DNA replication initiation in low-risk and high-risk HPVs. Our results demonstrate that HPV-encoded E2 initiator protein and its four binding sites in the replication origin play pivotal roles in determining the destiny of the HPV-infected cell. We have identified strain-specific single nucleotide variations in E2 binding sites found only in the high-risk HPVs. We have demonstrated that these variations result in attenuated formation of the E2-DNA complex. E2 binding to these sites is linked to the activation of the DNA replication origin as well as initiation of DNA replication. Both electrophoretic mobility shift assay and atomic force microscopy studies demonstrated that binding of E2 from either low- or high-risk HPVs with variant binding sequences lacked multimeric E2-DNA complex formation in vitro. These results provided a molecular basis of differential DNA replication in the two types of HPVs and pointed to a correlation with the development of cancer. [Display omitted] •High-risk (HPV-16) E2 protein bound to three of its four binding sites efficiently. The binding affinities are likely as follows: BS4>BS2≈BS1>>BS3.•A common feature amongst the high-risk genotypes was found to be a single nucleotide variation (SNV) in a E2 binding site (BS2 or BS3) which led to attenuation in E2 multimer formation on the origin DNA.•The SNVs in E2 binding sites in the origin correlated well with the HPV-associated carcinogenicity.•Based on the evidence presented here, a model for the interplay of E2 and its binding sites in HPV DNA replication and modulation of carcinogenicity was proposed.